Physiological and perceived sleep recovery comparison of 19 to 24- year-old elite hockey players - Middoni Martinez, G.; Hauernherm, F. J. (Satakunta University of Applied Sciences, 2020)
Sleep is an essential part of recovery and hence also of high importance for athletic performance and health. While most athletes and coaches are aware of this fact, studies have shown that athletes often have difficulties achieving adequate sleep length and/or - quality. Possible reasons for sleep issues include, among others, neurological stimulants (e.g. stadium light, caffeine, blue light), travel, pre-game anxiety or the unfamiliar environment of hotel rooms. This study aimed to compare the physiological and perceived sleep recovery of eight 19- 24-year-old elite hockey players from the team Pori Ässät. Physiological findings were obtained using the Firstbeat Bodyguard 2 devices and perceived recovery was enquired through daily personal phone interviews. Measurements took place during a 5-day road trip, including 2 away game nights, and covered five nights in total. For technical reasons, physiological measurements only provided sufficient data for six out of eight players. The six players were, in contrast to previous studies, able to achieve the minimum recommended amount of seven hours total sleep time (TST) per night. TST was slightly lower on game nights than on non-game nights. Firstbeat data demonstrated that all players achieved good sleep recovery, despite the fact that interviews showed that none of them followed any particular sleep routine and most consumed caffeine up until the evening. Interviews furthershowed that players` perceived sleep quality and recovery were in line with the physiological findings, although the perceived recovery was slightly lower than the Firstbeat data would suggest. In summary, all six examined players recovered well during the night. Coaches can use the data of this study to further develop training intensities and plan for rest and recovery days. They can also use the results to further educate players on the importance of good sleep hygiene.